Risk Management Analysis and Mitigation Strategies for the Self-Heating Coal Phenomenon in Coal Loading Operations - Akbar Yasser Al Rashid; I'ie Suwondo; Trisnowati Rahayu; Fazri Hermanto (Newinera Publisher, 2026)
The phenomenon of coal self-heating represents a critical risk during loading operations at Muara Jawa Port, as it can lead to temperature escalation, smoke generation, and potential fire hazards. This study examines the causes of coal self-heating, assesses its risk level, and evaluates the conformity of handling practices with the IMSBC Code and the IMDG Code. A descriptive qualitative approach was employed, involving direct observation aboard MV Golden Ace, temperature measurements using a thermal scanner, and risk analysis through Hazard Identification and Risk Assessment (HIRA). The findings indicate that coal temperatures reached 61°C, exceeding the safe threshold of 55°C as stipulated by the IMSBC Code, thereby necessitating the suspension of loading operations to allow for cooling. The HIRA results identify the highest risk phase occurring during the transfer of coal from barges to grab cranes, due to increased exposure to air and high humidity levels. While several operational procedures were found to be compliant with existing regulations, shortcomings remain in temperature documentation and gas monitoring practices. This study underscores the importance of early detection, continuous temperature surveillance, and effective mitigation strategies to enhance operational safety in coal loading activities.